2018
DOI: 10.3329/baj.v21i1.39361
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Annual Weeds Against Metolachlor + Bensulfuron - Methyl Herbicide in Transplanted Rice

Abstract: Field trials were conducted at Bangladesh Rice Research Institute (BRRI), Gazipur during aman, 2014 and boro, 2014-15 to evaluate the efficacy of metolachlor + bensulfuron methyl 20% WP on weed suppression of transplanted rice. Metolachlor + bensulfuron methyl 20% WP @ 150, 190 and 230 g ha-1 were applied and pyrazosulfuran ethyl @ 125 g ha-1, weed free and unweeded control were the treatment variables. Visual observations indicated that this herbicide possesses high selectivity and not toxic to rice pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Angiras and Kumar (2005) also found that the application of pyrazosulfuron ethyl showed no phytotoxic effect on rice plants. Bhuiyan et al (2018) reported no phytotoxic symptoms on rice with the application of combined herbicide like Metolachlor + bensulfuron methyl. Zahan et al (2014) found a non-hazardous effect of pretilachlor on transplanted Aman rice crop production.…”
Section: Phytotoxicity Of Herbicides On Rice Plantmentioning
confidence: 98%
“…Angiras and Kumar (2005) also found that the application of pyrazosulfuron ethyl showed no phytotoxic effect on rice plants. Bhuiyan et al (2018) reported no phytotoxic symptoms on rice with the application of combined herbicide like Metolachlor + bensulfuron methyl. Zahan et al (2014) found a non-hazardous effect of pretilachlor on transplanted Aman rice crop production.…”
Section: Phytotoxicity Of Herbicides On Rice Plantmentioning
confidence: 98%